Tyrosine Kinase Inhibitors-Induced Arrhythmias: From Molecular Mechanisms, Pharmacokinetics to Therapeutic Strategies - Mengfei Cheng (Frontiers Media S.A., 2021)
With the development of anti-tumor drugs, tyrosine kinase inhibitors (TKIs) are an indispensable part of targeted therapy. They can be superior to traditional chemotherapeutic drugs in selectivity, safety, and efficacy. However, they have been found to be associated with serious adverse effects in use, such as myocardial infarction, fluid retention, hypertension, and rash. Although TKIs induced arrhythmia with a lower incidence than other cardiovascular diseases, much clinical evidence indicated that adequate attention and management should be provided to patients. This review focuses on QT interval prolongation and atrial fibrillation (AF) which are conveniently monitored in clinical practice. We collected data about TKIs, and analyzed the molecule mechanism, discussed the actual clinical evidence and drug-drug interaction, and provided countermeasures to QT interval prolongation and AF. We also pooled data to show that both QT prolongation and AF are related to their multi-target effects. Furthermore, more than 30 TKIs were approved by the FDA, but most of the novel drugs had a small sample size in the preclinical trial and risk/benefit assessments were not perfect, which led to a suspension after listing, like nilotinib. Similarly, vandetanib exhibits the most significant QT prolongation and ibrutinib exhibits the highest incidence in AF, but does not receive enough attention during treatment.